Epidemic context, covid situation and creative shaping of Urdu fiction - Ilyas Kabeer; Dr.Saira Irshad (Zaban-o-Adab, 2021)
In post-colonial societies, when epidemics arise, along with these epidemics, the multinational corporations emerging from the corporate sector begin to emerge with all their exploitative torments, while on the one hand, the possibilities, implications and fears of the epidemic begin to emerge. At the same time, such multinational institutions appear in our society. In this context, while literature has found a new direction, Urdu fiction could not remain unmindful, keeping in view the context in which we have been able to declare them as saviors from this epidemic. The themes of Urdu fiction open new doors of thought besides connecting with society.